Innovation Model Of Electronic-Based Business Licensing Services At The One-Door Integrated Service Investment Office Of Bengkulu Province - Pranata, Yuvaldo Dimas; Alexander, Alexander; Aprianty, Henny (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The increasing needs of the community and the presence of technology that can make it easier, therefore the Bengkulu Provincial Government, especially DPMPTSP, created an innovation to facilitate the provision of business licensing services for the community in the form of the SIPANSE application. The SIPANSE application is a digitalization of licensing affairs by serving an integrated system, online system, digital signature, and mobile system. Innovation is the entire process of creating and offering new things that are discovered. SIPANSE innovation is not immediately applied, but requires a certain process. The purpose of this study was to analyze the model and process of licensing service innovation through SIPANSE and to analyze the supporting and inhibiting factors of the innovation process. The method used in this study is descriptive qualitative. Data collection techniques were carried out through observation, documentation and interviews with several informants selected by purposive sampling. The results of the study showed that the SIPANSE innovation process had been carried out well, at the initiation stage it was carried out through various activity processes such as coordination meetings, socialization, providing information, technical guidance and training. In the second stage, namely the implementation of steps taken through various processes including the inauguration of the SIPANSE application, adding application features, creating a guidebook, providing information and consultation rooms, and further socialization through social media, official websites and participation in reality shows. This Implementation Stage also includes the provision of complaint forms, evaluation of service implementation, and development of the SIPANSE application IMB menu for the sustainability of innovation. Driving factors for the SIPANSE innovation process, namely the support of facilities and infrastructure and the support of parties involved and responsible. Inhibiting factors for the SIPANSE innovation process, namely the lack of incentives for employees.